The Saga of Pandemics through the Literary Lens - Sen, Nandini C; Chawla, Abhay (Nusantara Journal of Behavioral and Social Science, 2023)
Disease, illness and death have been a human being’s constant companion right from the dawn of civilization and Pandemics are a part of this fatal manifestation which has been witnessed century upon century, successfully wreaking havoc upon the unsuspecting mankind. A pandemic (from Greek - pan, meaning "all" and demos meaning "people") is an epidemic of an infectious disease that has spread across a large region, spreading through continents and killing with impunity as it spreads. Throughout human history, there have been a number of pandemics of diseases such as smallpox and tuberculosis. The most fatal pandemic in recorded history was the Black Death (also known as The Plague), which killed an estimated 75–200 million people in the 14th century. Other notable pandemics include the 1918 pandemic, the Spanish influenza (Spanish flu). The current pandemics include Covid19 and HIV AIDS. The history of pandemic has been recorded meticulously by playwrights, novelists and poets from time immemorial – the documentation is detailed and, on some occasions, laboured. The message conveyed is very clear – the pandemic is brutal, it spares no one and the only way to remain safe is through isolation and timely medical intervention. This Paper seeks to examine the philosophical ramifications of pandemics examined through the literary lens.